Improving Pancasila Education Learning Outcomes Using the Problem Based Learning Model Assisted by Google Sites Media - Hafizatul Wardiah; Putera, Rafhi Febryan (Journal of Practice Learning and Educational Development, 2025)
This research was motivated by the low learning outcomes of students in Pancasila Education, which was due to teachers not yet utilizing innovative learning models that could attract students' attention during lessons. The purpose of this study was to describe the improvement in Pancasila Education learning outcomes through the use of the Problem Based Learning model assisted by Google Sites media. This research was a classroom action research (CAR) conducted at SDN 17 Sungai Pandahan, Pasaman Regency, employing both qualitative and quantitative approaches. The study was carried out in two cycles, with Cycle I consisting of two meetings and Cycle II consisting of one meeting. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The subjects of this study were the teacher and fourth-grade students of SDN 17 Sungai Pandahan, with a total of 20 students — 9 male and 11 female students. Data collection techniques included observation, tests, and non-test instruments. The results of this study were based on the recapitulation tables of the results from Cycle I and Cycle II as presented in the discussion section. The findings showed an improvement in: a) the teaching module, with an average of 84.37% qualification (good) in Cycle I, increasing to 96.87% with a qualification of (very good) in Cycle II; b) the implementation aspect for teachers, with an average of 80.35% qualification (sufficient) in Cycle I, increasing to 96.42% with a qualification of (very good) in Cycle II, and for students, with an average of 80.35% qualification (sufficient) in Cycle I, increasing to 96.42% with a qualification of (very good) in Cycle II; c) the students' learning outcomes, with an average score of 77.42 (sufficient) in Cycle I, increasing to 90.24 (good) in Cycle II. Based on these results, it can be concluded that using the Problem Based Learning model assisted by Google Sites media can improve students' learning outcomes in Pancasila Education.